Etude phytochimique et antibactérienne du genre marrubium vulgare De la région de souk ahras - nouaouia Fairouz; Atarsia khaoula (My University, 2019)
Our Works was done on an aromatic and medicinal plant The white horehound (Marrubium vulgare), family Lamiaceae , is a plant perennial herbaceous, spontaneous very responded in the region ain sanour (souk ahras) This work was carried out on an ethnobotanical survey and soil analysis to arrive a histological study, thus relates to a photochemical screening of the var ious preparations of the aerial part of white horehound (Marrubium vulgare) which revealed the wealth of this plant in tannins and in reducing compounds, saponoside, flavonoids and sterols and terpenoids, in the end an antibacterial study and tests polyphenols. ------------------------------------------------------------------------------------------- يدور هذا العمل حول نبتة عطرية طبية Marrubium vulgare من عائلة Lamiacee ، هذه النبتة عشبية معمرة عشوائية، موجودة بكثرة في منطقة عين سنور (سوق أهراس). تم هذا العمل بإجراء خاص بالنبتة في هذه المنطقة تحليل التربة من ثم الوصول إلى الدراسة النسيجية،و أيضا دراسة كيميو نباتية و أخيرا النشاط المضاد للبكتيريا . ------------------------------------------------------------------------ Ce travail a été réalisé sur la base d'une enquête ethnobotanique et d'une analyse de sol pour arriver à un étude histologique, concerne donc un criblage photochimique de la var préparations judicieuses du partie aérienne du marrube blanc (Marrubium vulgare) qui a révélé la richesse de cette plante en tanins et en composés réducteurs, saponoside, flavonoïdes et stérols et terpénoïdes, dans le terminer une étude antibactérienne et tester polyphenols.